Fast automatic multiscale electron tomography for sensitive materials under environmental conditions - Louis-Marie Lebas; Karine Masenelli-Varlot; Victor Trillaud; Cédric Messaoudi; Mimoun Aouine; Laurence Burel; Valentine Noblesse; Clémentine Fellah; Erwan Allain; Christophe Goudin; José Ferreira; Matthieu Amor; et al. (Communications Engineering)
Abstract The demand for characterisation of beam-sensitive samples at the nanoscale in environmental conditions is increasing for applications in materials science and biology. Here we communicate a protocol with custom software, enabling precise control over the electron microscope, and a custom sample holder, facilitating automated acquisition of fast 3D data from a single object under environmental conditions. This method enables imaging with a controlled electron dose and multi-modal electron signals. The method can be used in environmental scanning or transmission electron microscopes for easy sample preparation and to benefit from high spatial resolution, respectively. To demonstrate its effectiveness, we investigate the porosity of Al(OH)3 hydrogels, and the penetration ability and distribution of gold nanoparticles. Unfixed, hydrated magnetotactic bacteria producing intracellular iron oxide nanoparticles were also characterized in 3D in their native state. This methodological and technical development serves as a milestone in the study of various samples at any humidity level, offering easier sample preparation compared to cryo-TEM techniques, while maintaining a similar or even lower dose level.